1997
DOI: 10.1152/ajpregu.1997.273.2.r823
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide stimulation of the nitric oxide signaling pathway in Drosophila melanogaster Malpighian tubules

Abstract: Activation of the nitric oxide (NO) and guanosine 3', 5'-cyclic monophosphate (cGMP) signaling pathway stimulates fluid secretion by the Drosophila melanogaster Malpighian tubule. The neuropeptide cardioacceleratory peptide 2b (CAP2b) has been previously shown to stimulate fluid secretion in this epithelium by elevating intracellular cGMP levels. Therefore, it was of interest to investigate if CAP2b acts through NO in isolated tubules and thus presumably through stimulation of a tubule NO synthase (NOS). We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 0 publications
3
45
1
Order By: Relevance
“…It has been shown that Drosophila CAP2b-1 and -2 act on principal cells of malphighian tubules, stimulating fluid secretion through the calcium-nitric oxide-cGMP pathway (33)(34)(35)(36). It will be interesting to determine whether CG14575, the putative CAP2b-1͞CAP2b-2 receptor from this study, is expressed in Malpighian tubules.…”
Section: Drosophila Gpcrs In the Nmur Group Are Activated By Prxa Pepmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that Drosophila CAP2b-1 and -2 act on principal cells of malphighian tubules, stimulating fluid secretion through the calcium-nitric oxide-cGMP pathway (33)(34)(35)(36). It will be interesting to determine whether CG14575, the putative CAP2b-1͞CAP2b-2 receptor from this study, is expressed in Malpighian tubules.…”
Section: Drosophila Gpcrs In the Nmur Group Are Activated By Prxa Pepmentioning
confidence: 99%
“…For example, early demonstrations of activity for the pyrokinins (FXPRXa) were based on stimulation of gut, oviduct, and heart (5, 24), whereas more recent data implicating them in pheromone biosynthesis (6) and cuticle melanization (7) are more suggestive of authentic physiological functions. The FPRXa peptides, including small cardioactive peptides and cardioacceleratory peptide (CAP2b), were isolated based on their activity in heartbeat modulation (8,9) but may be involved in water and ion transport (33,34,36). Finally, although all other PRXa peptides are produced in the central nervous system (CNS) (44,45), ETH (PRXa) is produced peripherally in epitracheal Inka cells (13) and acts on CNS to trigger central pattern generators leading to ecdysis behavior (14).…”
Section: Drosophila Gpcrs In the Nmur Group Are Activated By Prxa Pepmentioning
confidence: 99%
“…Both peptides, AWKSMNVAW-amide (predicted as Drm-MIP-2) and DQWQKLHGGW-amide (predicted as Drm-MIP 5), are amidated, which is in agreement with the C-terminal glycine residues in the precursor (Table II). Peptides Derived from the capability or capa Gene-Cardio acceleratory peptide 2b (CAP2b), first isolated from the tobacco hawkmoth Manduca sexta (21), displays cardio-acceleratory properties and stimulates Malpighian tubule secretion (22).…”
Section: Resultsmentioning
confidence: 99%
“…39 In addition to its cardio-acceleratory properties, it also stimulates Malpighian tubule secretion in D. melanogaster through activation of the nitric oxide (NO) and intracellular cGMP signaling pathways. 40 Related peptides were isolated from the perisympathetic organs of six different cockroach species. 41,42 These so-called periviscerokinins display a myotropic effect on the hyperneural muscle of Periplaneta americana.…”
Section: The Cardio Acceleratory Peptide or Capability Precursormentioning
confidence: 99%